Highly Stretchable Non-volatile Nylon Thread Memory - Kang, Ting-Kuo (Sci Rep, 2016)
Integration of electronic elements into textiles, to afford e-textiles, can provide an ideal platform for the development of lightweight, thin, flexible, and stretchable e-textiles. This approach will enable us to meet the demands of the rapidly growing market of wearable-electronics on arbitrary non-conventional substrates. However the actual integration of the e-textiles that undergo mechanical deformations during both assembly and daily wear or satisfy the requirements of the low-end applications, remains a challenge. Resistive memory elements can also be fabricated onto a nylon thread (NT) for e-textile applications. In this study, a simple dip-and-dry process using graphene-PEDOT:PSS (poly(3,4-ethylenedioxythiophene) polystyrene sulfonate) ink is proposed for the fabrication of a highly stretchable non-volatile NT memory. The NT memory appears to have typical write-once-read-many-times characteristics. The results show that an ON/OFF ratio of approximately 10(3) is maintained for a retention time of 10(6) s. Furthermore, a highly stretchable strain and a long-term digital-storage capability of the ON-OFF-ON states are demonstrated in the NT memory. The actual integration of the knitted NT memories into textiles will enable new design possibilities for low-cost and large-area e-textile memory applications.